Polychlorinated naphthalenes (PCNs) in Chinese forest soil: Will combustion become a major source? - Xu, Yue; Li, Jun; Zheng, Qian; Pan, Suhong; Luo, Chunling; Zhu, Haolin; Nizzetto, Luca; Zhang, Gan (Environmental pollution (Barking, Essex, 2015)
We collected O- and A-horizon soil samples in 26 Chinese mountainous forests to investigate the content, spatial pattern, and potential sources of polychlorinated naphthalenes (PCNs). Spatial patterns were influenced mainly by the approximation to sources and soil organic contents. High concentrations often occurred close to populated or industrialized areas. Combustion-related activities contributed to PCN pollution. Relatively high proportions of CN-73 in northern China may be attributed to coke consumption, while CN-51 could be an indicator of biomass burning in Southwest China. There are evidences that PCNs may largely derived from unintentional production. If uncontrolled, UP-PCN (unintentionally produced PCNs) emissions could increase with industrial development. The abnormally high concentrations at Gongga and Changbai Mountains appear to be associated with the high efficient of forest filter of atmospheric contaminants at these densely forested sites. We question whether this is caused by ecotones between forests, and raise additional questions for future analyses.
Keywords: China; spontánní samovznícení; Air Pollutants; Environmental Pollution; Naphthalenes; látky znečišťující vzduch; naftaleny; látky znečišťující půdu; Soil Pollutants; Chinese forest soil; Čína; půda; Spontaneous Combustion; PCNs; znečištění životního prostředí; Combustion-related sources; Soil; Ecotone; SOC